2012
DOI: 10.1038/oby.2012.66
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Placebo‐Controlled Clinical Trial of Lorcaserin for Weight Loss in Type 2 Diabetes Mellitus: The BLOOM‐DM Study

Abstract: Mellitus) study evaluated efficacy and safety of lorcaserin for weight loss in patients with type 2 diabetes. Secondary objectives included evaluations of glycemic control, lipids, blood pressure, and quality of life. This 1-year, randomized, placebo-controlled trial enrolled 604 patients 1:1:1 to placebo, lorcaserin 10 mg once daily (QD) or lorcaserin 10 mg twice daily (BID). Patients were treated with metformin, a sulfonylurea (SFU) or both; had glycated hemoglobin (HbA 1c ) 7-10%; were 18-65 years old; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
451
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(473 citation statements)
references
References 27 publications
13
451
2
5
Order By: Relevance
“…In overweight or obese patients without diabetes, lorcaserin treatment provided a 25.81% reduction from baseline body weight after 1 year versus 22.16% with placebo (P , 0.001) (79). Lorcaserin is a selective small-molecule agonist of the 5-hydroxytryptamine 2C serotonin receptor (5HT2C), which regulates mechanisms related to satiety, ingestive behavior, glucose tolerance, and hepatic insulin sensitivity (71). Unlike previously available antiobesity agents, lorcaserin has a low affinity for the 5HT2B receptor subtype, whose activation has been linked to the development of valvular heart disease (78).…”
Section: Lorcaserinmentioning
confidence: 99%
See 1 more Smart Citation
“…In overweight or obese patients without diabetes, lorcaserin treatment provided a 25.81% reduction from baseline body weight after 1 year versus 22.16% with placebo (P , 0.001) (79). Lorcaserin is a selective small-molecule agonist of the 5-hydroxytryptamine 2C serotonin receptor (5HT2C), which regulates mechanisms related to satiety, ingestive behavior, glucose tolerance, and hepatic insulin sensitivity (71). Unlike previously available antiobesity agents, lorcaserin has a low affinity for the 5HT2B receptor subtype, whose activation has been linked to the development of valvular heart disease (78).…”
Section: Lorcaserinmentioning
confidence: 99%
“…Unlike previously available antiobesity agents, lorcaserin has a low affinity for the 5HT2B receptor subtype, whose activation has been linked to the development of valvular heart disease (78). In a phase 3 study of subjects with type 2 diabetes treated with metformin or a sulfonylurea, lorcaserin treatment resulted in mean weight changes of 24.5% (twice daily) and 25.0% (once daily) compared with 21.5% with placebo at week 52 (71). Participants also showed a significant improvement in glycemic control: HbA 1c decreased 20.9% and 21.0% from baseline with lorcaserin twice daily and once daily, respectively, versus 20.4% with placebo (P , 0.001 for each lorcaserin dose).…”
Section: Lorcaserinmentioning
confidence: 99%
“…These effects help patients sustain weight loss and help them comply with calorie‐reduced diets. Clinical trials have shown that the addition of pharmacotherapy to lifestyle interventions promotes greater weight loss and sustains weight loss for a longer period of time than lifestyle interventions alone 13, 96, 97, 99, 100, 116. The available data, while only encompassing ≤2 years of follow‐up, demonstrate that these pharmacotherapies sustain weight loss while patients randomized to lifestyle interventions plus placebo are regaining weight (Table 1) 13, 96, 97, 99, 100, 116.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…34 Among patients with DM in the BLOOM-DM trial, lorcaserin improved HbA 1c more than placebo (−0.8 vs −0.3). 33 Bupropion Plus Naltrexone Bupropion plus naltrexone, which has not been approved by the FDA at the time of this writing, has demonstrated weight-loss efficacy in 4 phase III clinical trials (Table 1). This combination pill has been tested in 2 dosages, 360 mg of bupropion together with either 16 mg or 32 mg of naltrexone.…”
Section: Potential Benefits Of Modern Pharmacotherapy For Obesity Phementioning
confidence: 99%